Self-criticism, perfectionism and eating disorders: The effect of depression and body dissatisfaction - Ferreira, C. (2014)
Ferreira, C., Pinto-Gouveia, J., & Duarte, C. (2014). Self-criticism, perfectionism and eating disorders: The effect of depression and body dissatisfaction. International Journal of Psychology and Psychological Therapy, 14(3), 409-420. http://www.ijpsy.com/volumen14/num3/396.html